An Improved Enzyme-Linked Immunosorbent Assay (ELISA) Based Protocol Using Seeds for Detection of Five Major Peanut Allergens Ara h 1, Ara h 2, Ara h 3, Ara h 6, and Ara h 8 - Pandey, Arun K.; Varshney, Rajeev K.; Sudini, Hari K.; Pandey, Manish K. (Frontiers in Nutrition, 2019)
Peanut allergy is an important health concern among many individuals. As there is no effective treatment to peanut allergy, continuous monitoring of peanut-based products and their sources is essential. Precise detection of peanut allergens is key for identification and development of improved peanut varieties with minimum or no allergens in addition to estimating the levels in peanut-based products available in food chain. The antibody based ELISA protocol along with sample preparation was standardized for Ara h 1, Ara h 2, Ara h 3, Ara h 6 and Ara h 8 to estimate their quantities in peanut seeds. Three different dilutions were optimized to precisely quantify target allergen proteins in peanut seeds such as Ara h 1 (1/1000, 1/2000 and 1/4000), Ara h 2 and Ara h 3 (1/5000, 1/10,000 and 1/20,000), Ara h 6 (1/40,000, 1/80,000 and 1/1, 60,000) and Ara h 8 (1/10, 1/20 and1/40). These dilutions were finalized for each allergen based on the accuracy of detection by achieving <20% coefficient of variation in three technical replicates. This protocol captured wide variation of allergen proteins in selected peanut genotypes for Ara h 1 (77 - 46106 μg/g), Ara h 2 (265 - 5426 μg/g), Ara h 3 (382 - 12676 μg/g), Ara h 6 (949 - 43375 µg/g) and Ara h 8 (0.385 - 6 μg/g). The assay is sensitive and reliable in precise detection of five major peanut allergens in seeds. Deployment of such protocol allows screening of large scale germplasm genotypes while developing peanut varieties with minimum allergenicity to ensure food safety.